Facing it : AIDS diaries and the death of the author - Chambers, Ross. (Ann Arbor, Mich. ; [Great Britain] : University of Michigan Press, 1998)
Facing It examines the genre of the AIDS diary, not in classificatory terms but pragmatically, as the site of a social interaction. In this case, the interaction is between authors, whose subject is their own dying and death, and readers, for whom the act of reading becomes a form of mourning. Writing and reading are separated but also joined by the unthinkable, unsayable, unreadable event of death. That is, between them they enact a scenario of survival. Through a detailed study of three AIDS diaries, originating in France, the United States, and Australia, Ross Chambers demonstrates that issues concerning the politics of AIDS writing and the ethics of reading are linked by a common concern with the problematics of survivorhood. Finally, Facing It takes on the issue of its own relevance, asking what literary criticism can do in an epidemic.
1. Writing AIDS -- 2. Dying as an Author -- 3. Confronting It: La pudeur ou l'impudeur and the Phantom Image -- 4. An Education in Seeing: Silverlake Life -- 5. Anxious Reading: Eric Michaels's Unbecoming -- 6. RSVP, or Reading and Mourning.
Includes bibliographical references.
Keywords: AIDS (Disease) -- Patients -- Diaries